Culturable bacterial endophytes of Aconitum carmichaelii Debx. were diverse in phylogeny, plant growth promotion, and antifungal potential - Zou, Lan; Wang, Qian; Li, Muyi; Wang, Siyu; Ye, Kunhao; Dai, Wei; Huang, Jing (Frontiers in Microbiology, 2023)
Medicinal plants harbor tremendously diverse bacterial endophytes maintaining plant growth and health. In the present study, a total of 124 culturable bacterial endophytes were isolated from healthy Aconitum carmichaelii Debx. plants. These strains were clustered into 10 genera based on full-length 16S rDNA sequence, among which Bacillus and Pseudomonas were the dominant genera. In addition, A. carmichaelii may capture 10 potential new bacterial species based on multi-locus sequence analysis of three housekeeping genes (gyrA, rpoB and atpD). Majority of these bacterial endophytes exhibited plant growth promoting ability through diverse actions including production of either indole acetic acid, siderophore or hydrolytic enzymes (glucanase, cellulose and protease) and solubilization of phosphate or potassium. Twenty strains inhibited hyphal growth of fungal pathogens Sclerotium rolfsii and Fusarium oxysporum in vitro and on root slices of A. carmichaelii by dual-culture method, among which Pseudomonas sp. SWUSTb-19 showed the best antagonistic activity. Field experiment confirmed that Pseudomonas sp. SWUSTb-19 significantly reduced occurrence of southern blight and promoted plant biomass compared to non-inoculation treatment. The possible mode of actions for Pseudomonas sp. SWUSTb-19 to antagonize against S. rolfsii involved the production of glucanase, siderophore, lipopeptides and antimicrobial volatile compounds. Altogether, this study revealed that A. carmichaelii harbored diverse plant growth promoting bacterial endophytes and Pseudomonas sp. SWUSTb-19 could be served as potential biocontrol agent against southern blight.